Native or Web-Hybrid Apps? An Analysis of the Adequacy for Accessibility of Android Interface Components Used with Screen Readers - Carvalho, Lucas Pedroso Carvalho; Freire, André Pimenta Freire (Teste, 2018)
Creating accessible mobile applications involves several important design decisions in order to accommodate the needs of disabled users, especially people with visual disabilities who use screen readers. The goal of the study presented in this paper was to analyze the adequacy of interface components to implement mobile applications, in order to identify the main accessibility problems that could be encountered by developers when using them, and the main strategies to overcome those issues. We performed an accessibility evaluation of a sample of 30 Android interface components present in 3 prototypes of mobile applications, employing the development techniques of native applications with and withoug Web components and hybrid development using the Apache Cordova framework. The results showed that the prototypes developed using web components were more compatible with accessibility criteria in the Web Content Accessibility Guidelines (WCAG 2.0) and with the screen reader Talkback. The most frequent accessibility problems in such components occurred in tables, headings and multimedia elements. Based on the current challenges for accessibility in mobile applications, we highlight the limitations of some interface components and emphasize that more studies need to be carried out to consolidate accessibility guidelines and good practices for mobile devices.